Advancements and Clinical Significance of Breast Cancer Exosome Detection - Zhou, Xinjie (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Exosomes, which are lipid bilayer vesicles actively secreted by cells with a diameter of 30-100 nm, play a crucial role in the occurrence, development, and formation of the tumor microenvironment in breast cancer. They have become an important component of liquid biopsies for breast cancer and ideal targets for early diagnosis, treatment assessment, and clinical therapy. Breast cancer is the most common malignancy among women. However, traditional exosome detection methods have several limitations, and there are still many difficulties and challenges in achieving widespread clinical application of exosomes. Nowadays, significant progress has been made in exosome detection and analysis techniques, including optical methods such as colorimetry, fluorescence, surface-enhanced Raman scattering, as well as various electrochemical and thermal signal methods. This review summarizes the current biomarkers and novel developments in detection techniques applied to liquid biopsy of exosomes in breast cancer.